Fractionation and current time trends of PCB congeners: evolvement of distributions 1950–2010 studied using a global atmosphere-ocean general circulation model - G. Lammel; I. Stemmler (Atmospheric Chemistry and Physics, 2012)
PCBs are ubiquitous environmental pollutants expected to decline in abiotic environmental media in response to decreasing primary emissions since the 1970s. A coupled atmosphere-ocean general circulation model with embedded dynamic sub-models for atmospheric aerosols and the marine biogeochemistry and air-surface exchange processes with soils, vegetation and the cryosphere is used to study the transport and fate of four PCB congeners covering a range of 3–7 chlorine atoms. The change of the geographic distribution of the PCB mixture reflects the sources and sinks' evolvement over time. Globally, secondary emissions (re-volatilisation from surfaces) are on the long term increasingly gaining importance over primary emissions. Secondary emissions are most important for the congeners with 5–6 chlorine atoms. Correspondingly, the levels of these congeners are predicted to decrease slowest. Changes in congener mixture composition (fractionation) are characterized both geographically and temporally. In high latitudes enrichment of the lighter, less persistent congeners and more delayed decreasing levels in response to decreasing emissions are found. The delivery of the contaminants to high latitudes is predicted to be more efficient than previously suggested. The results suggest furthermore that the effectiveness of emission control measures may significantly vary among substances. The trends of decline of organic contaminant levels in the abiotic environmental media do not only vary with latitude (slow in high latitudes), but do also show longitudinal gradients.